FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PASANGAN USIA SUBUR (PUS) DALAM PENGGUNAAN KONTRASEPSI IUD PASKA SALIN DI RSU SEBENING KASIH - Nur Diana Shofiyati; Ana Zumrotun Nisak; Dwi Astuti (Rena Cipta Mandiri, 2026)
The high rate of population growth, which has not been accompanied by an improvement in the quality of the population, has led to efforts to address this issue through the Family Planning (KB) programme. One form of contraception is the IUD. This study aims to determine the factors that influence the interest of couples of childbearing age (PUS) in using IUD contraception. This study uses a quantitative correlational research design and a cross-sectional research design. The population consisted of 246 patients, and the sample size was 61 respondents. Data collection used a questionnaire to assess the factors influencing the interest of couples of childbearing age (PUS) in using IUD contraception. The results showed that of the 61 respondents, 33 respondents (54%) had low interest and 28 respondents (46%) had high interest in IUDs. Spearman's rank analysis showed that there was a relationship between interest in IUD use and education (p-value 0.004), parity (p-value 0.014), husband's support (p-value 0.014), and culture (p-value 0.005).